2013
DOI: 10.1002/14651858.cd008569.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Percussion, diuresis, and inversion therapy for the passage of lower pole kidney stones following shock wave lithotripsy

Abstract: Percussion, diuresis, and inversion therapy for the passage of lower pole kidney stones following shock wave lithotripsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…So, if the treated kidney's function has deteriorated due to the obstruction, the dehydration hinders adequate urine flow around the stone [18]. Diuretics will increase urine flow and thus the probability of cavitation [19,20]; which means, pieces of the broken stone shell increase, and the centre of the stone is exposed to subsequent shockwaves allowing entry of urine through the broken surface, thus giving an adequate interface with the centre of the stone [15]. The size of the stone is an important prognostic factor for successful ESWL and is considered as a highly effective treatment option for lower pole stones ≤2 cm [21].…”
Section: Discussionmentioning
confidence: 99%
“…So, if the treated kidney's function has deteriorated due to the obstruction, the dehydration hinders adequate urine flow around the stone [18]. Diuretics will increase urine flow and thus the probability of cavitation [19,20]; which means, pieces of the broken stone shell increase, and the centre of the stone is exposed to subsequent shockwaves allowing entry of urine through the broken surface, thus giving an adequate interface with the centre of the stone [15]. The size of the stone is an important prognostic factor for successful ESWL and is considered as a highly effective treatment option for lower pole stones ≤2 cm [21].…”
Section: Discussionmentioning
confidence: 99%
“…If the function of the treated kidney has deteriorated because of the obstruction, dehydration hinders adequate urine flow around the stone. Diuretics increase the probability of cavitation by increasing this urine flow 5. Providing diuresis during SWL seems to be beneficial in providing this deep penetration.…”
Section: Discussionmentioning
confidence: 99%
“…From the experience of SWL to lower pole stones, mechanical percussion in an inverted position with diuresis can aid the passage of stone fragments from the lower pole, 177-179 yet a Cochrane review suggested further well-designed and adequately powered studies should be carried out to inform clinical practice. 180 A contralateral head-down tilt position after fURS was shown to significantly improve the stone-free rates. 181 Transcutaneousfocused ultrasonic pulses were also shown to help post-lithotripsy patients to pass stones, although further study on the use of this technology is required before generalized clinical use.…”
Section: Complicationsmentioning
confidence: 93%